2009
DOI: 10.1109/tip.2009.2026678
|View full text |Cite
|
Sign up to set email alerts
|

Color Image Segmentation by the Vector-Valued Allen–Cahn Phase-Field Model: A Multigrid Solution

Abstract: We present an efficient numerical solution of a PDE-driven model for color image segmentation and give numerical examples of the results. The method combines the vector-valued Allen-Cahn phase field equation with initial data fitting terms with prescribed interface width and fidelity constants. Efficient numerical solution is achieved using a multigrid splitting of a finite element space, thereby producing an efficient and robust method for the segmentation of large images. We also present the use of adaptive … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
19
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(19 citation statements)
references
References 30 publications
(74 reference statements)
0
19
0
Order By: Relevance
“…This idea has been extended for the vector-valued Allen-Cahn equation [34]. Recently,in [30] this technique is applied to problems in image segmentation. A review on various multigrid methods for obstacle problems can be found in [23].…”
Section: Preconditioning For the Allen-cahn Equationmentioning
confidence: 99%
See 1 more Smart Citation
“…This idea has been extended for the vector-valued Allen-Cahn equation [34]. Recently,in [30] this technique is applied to problems in image segmentation. A review on various multigrid methods for obstacle problems can be found in [23].…”
Section: Preconditioning For the Allen-cahn Equationmentioning
confidence: 99%
“…The scalar Allen-Cahn equation describes the motion of an interface separating two phases. In practical applications often more than two phases occur [7,18,30] and the phase field concept has been extended to deal with multi phase systems [17]. There a vector-valued order parameter u : Ω → R N is introduced, where each u i describes one phase, i.e.…”
mentioning
confidence: 99%
“…The Allen-Cahn model (or phase field model) has a variety of applications, e.g. in materials science, image processing, biology and geology, see [6,11,14,23,25,30,39]. In many of these applications more than two phases occur.…”
Section: Introductionmentioning
confidence: 99%
“…Chan, Y. S., see Toni, L., 2476-2490 T Tafti, P. D., Van De Ville, D., and Unser, M., Invariances, Laplacian-Like Wavelet Bases, and the Whitening of Fractal Processes; TIP April 2009 689-702 Tagliasacchi, M., Valenzise, G., and Tubaro, S., Hash-Based Identification of Sparse Image Tampering; 2491-2504 Tai, X.-C., see Han, S., TIP Oct. 20092289-2302 Takeda, H., see Protter, M., TIP Jan. 2009 36-51 Takeda, H., Milanfar, P., Protter, M., and Elad, M., Super-Resolution Without Explicit Subpixel Motion Estimation;1958-1975., see 2153-2166 Tan, T., see Yu, S., TIP Aug. 20091905-1910 Tanaka, Y., Ikehara, M., and Nguyen, T. Q., Multiresolution Image Representation Using Combined 2-D and 1-D Directional Filter Banks; TIP Feb. 2009 269-280 Tang, S., see 1563-1572 Tang, X., see Yan, S., TIP Jan. 2009 202-210 Tang, X., see Wang, H., TIP Jan. 2009 140-150 Tang, X., see Yan, S., TIP March 2009 670-676 Tang, X., see 2153-2166 Tang, Y., see Tian, J., TIP Oct. 20092355-2363 Tang, Y. Y., see Zhang, T., TIP Nov. 2009 Kay, D. A., TIP Oct. 20092330-2339 Toni, L., Chan, Y. S., Cosman, P. C., and Milstein, L. B., Channel Coding for Progressive Images in a 2-D Time-Frequency OFDM Block With Channel Estimation Errors; 2476-2490 Tourneret, J.-Y., see 2059-2070 Tran, T. D., see Sun, G., TIP May 2009 Qu, G., TIP Feb. 2009 435-440 Wang, D., see Han, S., TIP Oct. 20092289-2302 Wang, G., Schultz, L. J., and Qi, J., Bayesian Image Reconstruction for Improving Detection Performance of Muon Tomography; 1080-1089 Wang, H., see Yan, S., TIP Jan. 2009 202-210 Wang, H., …”
mentioning
confidence: 99%
“…-1910 Wu, X., see Zhang, L., TIP April 2009 797-812 Wu, X., Zhang, X., and Wang, X 2303-2315 Zerubia, J., see 1830-1843 Zhai, J., see 1936-1945 Zhang, C., see 1623-1632 Zhang, C., see 1623-1632 Zhang, D., see Zhang, L., TIP April 2009 797-812 Zhang, F., Wu, X., Yang, X., Zhang, W., and Zhang, L 1946-1957 Color Image Segmentation by the Vector-Valued Allen-Cahn Phase-Field Model: A Multigrid Solution. Kay, D. A., +, TIP Oct. 2009 Wang, H., +, TIP Feb. 2009 225-240 Interpolation An Adaptable k-Nearest Neighbors Algorithm for MMSE Image Interpolation. 1976-1987 An MRF-Based DeInterlacing Algorithm With Exemplar-Based Refinement.…”
mentioning
confidence: 99%